Pt and Pd on activated carbon for oxidation of 5-hydr oxymethylfurfural to 2,5-furandicarboxylic acid (2017)
(Eng) In this work the transformation in liquid phase of 5-hydroxymethylfurfural (5-HMF) to 2,5-furandicarboxylic acid was studied with the use of Pt and Pd catalysts supported on activated carbon with the presence of NaOH or CaCO3. The catalysts were characterized by H2 chemisorption at room temperature, X-ray spectroscopy (XPS) and thermogravimetric analysis (TGA). The results indicate that the particle size of the catalysts follows the order PtCl / C <PdCl / C <PdN / C which is closely related to the catalytic activity. Metallic particles were found to be present as Pd0 and Pt0 species. The catalyst being Pt-Cl / C with the use of CaCO3 as an additive.